Analisis Implementasi Pengendalian Waktu Dan Biaya Pada Pelaksanaan Pembangunan Gedung C Fkip Tahap III Universitas Lampung Dengan Metode Earned Value: Metode Nilai Hasil, Gedung C FKIP, Pengendalian Proyek, Waktu, Biaya - Ike Novita Sari; Ika Kustiani; Amril Ma'ruf Siregar (Jurusan Teknik Sipil Universitas Lampung, 2024)
Infrastructure is the main support in improving education in Indonesia. University of Lampung carries out routine the constraction and renovation of buildings to support educational facility needs. In order of construction project activities on schedule and on budget, so project control is needed as in construction for building C FKIP Phase 3 University of Lampung of the was carried out using the earned value method. This research aims to analyze cost and time performance by implementing earned value analysis, as well as knowing the variance in the Phase 3 FKIP Building C building project University of Lampung. The data used in this research is secondary data in the form of time scheduling, RAB, plan drawings, and weekly project progress reports. The results of the research show that the planned time for the construction contract for Building C FKIP Phase 3 University of Lampung, is 120 calendar days and this time is by the Estimate at Schedule calculation results in the last week. The estimated total time for project completion is 120 calendar days, which means the project was completed on time and did not experience additional time during construction or it could also be called on schedule. The actual costs incurred by the contractor were 9.56307021468% lower than the planned and the value of the work completed by the contractor.